2015
DOI: 10.1002/cam4.405
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second malignancies in patients with early‐stage classical Hodgkin's lymphoma treated in a modern era

Abstract: Second malignancies remain an issue affecting morbidity and mortality in long-term survivors of early stage Hodgkin's lymphoma (HL). We undertook this study to determine if treatment in the modern era resulted in decreased second malignancies. Patients diagnosed with stage I–II cHL between 1988 and 2009 who received radiation therapy (RT) were selected from the Surveillance, Epidemiology, and End Results (SEER) database. Freedom from second malignancy (FFSM) was estimated using the Kaplan–Meier method. Univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This event has already been reported in dogs and people with lymphoma. The causes underlying the development of second malignancies are still unclear, but treatment, above all alkylating agents, has been associated with subsequent malignant neoplasms in human medicine . Two of three dogs developing second malignancy in this study had received alkylating chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…This event has already been reported in dogs and people with lymphoma. The causes underlying the development of second malignancies are still unclear, but treatment, above all alkylating agents, has been associated with subsequent malignant neoplasms in human medicine . Two of three dogs developing second malignancy in this study had received alkylating chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…Our group and others (7, 12) also found that these disparities in treatment were associated with worse survival. Despite the survival benefits of radiation, this therapy has been associated with subsequent primary malignancies (6, 7, 21), an outcome that we were able to consider in our analyses. Specifically, we found that a somewhat higher proportion of patients who received radiation for their HL had subsequent cancer (4.9% versus 6.9%), which was associated with worse overall survival (data not shown); modern treatments with lower doses of radiation (7) may result in fewer subsequent cancers (21) and should continue to be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the survival benefits of radiation, this therapy has been associated with subsequent primary malignancies (6, 7, 21), an outcome that we were able to consider in our analyses. Specifically, we found that a somewhat higher proportion of patients who received radiation for their HL had subsequent cancer (4.9% versus 6.9%), which was associated with worse overall survival (data not shown); modern treatments with lower doses of radiation (7) may result in fewer subsequent cancers (21) and should continue to be monitored. However, even after controlling for initial treatment and subsequent cancers, we still observed differences in survival by race/ethnicity, neighborhood SES and health insurance, suggesting that other factors are influencing these associations.…”
Section: Discussionmentioning
confidence: 99%
“…80 This might be advantageous in the commonly young female patients with PMBL since mediastinal radiotherapy has potentially serious late effects, such as cardiovascular disease, lung cancer, and breast cancer. 81 For patients with MGZL, DA-EPOCH-R treatment alone may not be sufficient since they more often required additional radiation to achieve long term complete remission than patients with PMBL. 80 …”
Section: Novelties In the New Who Classification Of Mediastinal Tumorsmentioning
confidence: 99%